Growing compassion in poverty: Understanding self-compassion among underprivileged college students in Jakarta - Bijak Aditia Hutomo; Lussy Dwiutami Wahyuni; Santi Yudhistira (Priviet Social Sciences Journal, 2026)
Financial restraints are among the most obvious problems faced by college students from low socioeconomic backgrounds, as insufficient economic resources can impair not only academic progress but also psychological well-being. This study aimed to provide an overview of self-compassion among poor undergraduate students. This study used a cross-sectional, quantitative, and descriptive methodology. Two hundred ninety-five underprivileged college students from Jakarta, Indonesia, participated in this study. This study used a self-compassion measure to collect data on self-compassion, along with demographic information (gender, age, and household income). The results show that college students from disadvantaged backgrounds typically exhibit high levels of self-compassion. Analysis of the dimensions showed varying tendencies in self-kindness (moderate to high), common humanity (moderate to high), mindfulness (moderate to high), self-judgment (low to moderate), isolation (moderate), and over-identification (low to high), reflecting a balanced combination of compassionate and uncompassionate self-responding. Furthermore, additional analyses revealed no significant differences in overall self-compassion across demographic variables, including gender, age, and parental income. These results suggest that, despite the economic limitations they experience, underprivileged students can maintain a relatively high level of self-compassion, which may help them navigate academic pressures and financial stress more adaptively. This study highlights the importance of exploring strengths among underprivileged youth. This study provides a basis for future research on the role of self-compassion in promoting psychological resilience among disadvantaged student populations.